Integrasi Permainan Tradisional Layang-Layang dalam Pembelajaran Geometri di Madrasah Ibtidaiyah Roudlotul Huda Terban (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the integration of traditional kite flying into geometry lessons at Madrasah Ibtidaiyah Roudlotul Huda Terban. As a cultural activity rich in geometric elements—such as shapes, angles, and symmetry—kite flying offers a meaningful context for learning. Using a two-cycle Classroom Action Research (CAR) approach, data were gathered through observation, interviews, and documentation. The results showed that incorporating this activity improved students' understanding of geometry, increased engagement, and fostered a positive attitude toward mathematics. It also supported character education by promoting local cultural values. The study concludes that traditional games can be effective, culturally relevant tools for enhancing visual and spatial learning, and recommends that teachers develop similar innovative models to enrich education.